WRITING GRAMMATICAL SENTENCES: VOICES OF INDONESIAN UNDERGRADUATES IN EFL CLASSROOMS - Gai Mali, Yustinus Calvin (Universitas Pendidikan Indonesia, 2016)
Abstract This study aims to explore perspectives of Indonesian undergraduates on factors that conceivably help them to write grammatical English sentences. The participants of the study were 40 students in a Procedural Writing class and an Extensive Reading class, at English Language Education Study Program, Dunia University, Indonesia (ED-DU); academic year 2014/2015. The data were collected through students’ written responses and interview. More specifically, the students responded to a statement asking their perspectives towards the issue. In the interview process, the researcher asked 3 participants to provide further clarification of the responses they have written. The findings provide some evidence that friends’ feedback, sufficient time to practice, and lecturer’s feedback are the primary factors perceived by the students. Besides, the overall results of the study would seem to indicate that possessing grammatical competence, specifically in writing the grammatical sentences, needs conscious focus on grammatical aspects through explicit learning of grammar rules and sufficient time to practice the rules, which the study posits as conceivable ways to enhance the students’ grammatical accuracy. Eventually, the study proposes possible pedagogical ideas to help the students to minimize their grammatical errors, as an attempt to support their roles as a future professional English teacher and language user. Keywords: grammar, grammatical sentence, explicit learning, practice AbstrakPenelitian ini bertujuan untuk menyelidiki pandangan dari mahasiswa calon sarjana di Indonesia tentang faktor yang dapat membantu mereka untuk menulis kalimat bahasa Inggris dengan tata bahasa yang benar. Peserta dalam kajian ini adalah 40 mahasiswa di salah satu kelas Procedural Writing dan Extensive Reading, pada Program Studi Pendidikan Bahasa Inggris, Universitas Dunia Indonesia, tahun akademik 2014/2015. Data penelitian diambil dari respon tertulis mahasiswa dan wawancara. Secara lebih rinci, para mahasiswa merespon suatu pernyataan yang menggali pandangan mereka terkait dengan pokok persoalan tersebut. Dalam proses wawancara, peneliti meminta 3 peserta dalam kajian ini untuk menjelaskan lebih jauh tentang respon tertulis mereka. Hasil analisa data memberikan beberapa fakta bahwa umpan balik teman, waktu yang cukup untuk berlatih, dan umpan balik guru merupakan faktor utama yang disebutkan oleh para mahasiwa. Selain itu, keseluruhan hasil dari kaijan ini nampak mengindikasikan bahwa memiliki kompetensi ketatabahasaan, khususnya dalam menulis kalimat dengan tata bahasa yang benar, memerlukan fokus secara sadar pada aspek-aspek tata bahasa melalui pembelajaran eksplisit aturan ketatabahasaan dan waktu yang cukup untuk berlatih aturan tersebut. Pada akhirnya, kajian ini mengusulkan beberapa gagasan pedagogi yang mungkin dapat membantu para mahasiswa dalam mengurangi kesalahan tata bahasa mereka, sebagai suatu usaha untuk menunjang peran mereka sebagai guru bahasa Inggris dan pengguna bahasa yang profesional di masa yang akan datang.Kata kunci: tata bahasa, kalimat dengan tata bahasa yang benar, pembelajaran secara eksplisit, latihan